PENGEMBANGAN MODUL KIMIA BERBASIS POE (PREDICT, OBSERVE, AND EXPLAIN) PADA MATERI SIFAT KOLIGATIF LARUTAN SEBAGAI SUMBER BELAJAR PESERTA DIDIK KELAS XII SMA/MA - Roza Novia Putri; Erviyenni Erviyenni; Betty Holiwarni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The development of POE-based chemical modules on the colligative properties of the solution aims to obtain a valid chemical module based on the content feasibility, language, graphics, and presentation aspects. The research method of developing chemical module using 4-D model consists of four stages: Define (define) stage, Design stage, Development stage and Desseminate stage. However, in the implementation of research only to the stage of development. Data collection techniques using validation sheets given to two validators aim to assess the chemical modules that have been developed. The result of the research shows the acquisition of feasibility aspect of content 97.01%; 100% language feasibility aspect; aspect of 97.91% feasibility of aquality; and the feasibility aspect of 98.21% presentation. So the average validation score of all POE based chemical modules on the colligative nature of the solution is 96.7975% with very good category (very valid). Valid chemical modules are then tested to respondents. The respondents were limited to 4 chemistry teachers from SMA N 5 Pekanbaru and SMA N 8 Pekanbaru and 20 students from SMA N 5 Pekanbaru and SMA N 8 Pekanbaru. Analysis of user response data based on teachers 'sheets and learners' respective responses scored 93.667%. and 89.53%. Average overall validation scores and limited validity testing of chemical modules based on content feasibility, language, graphics, and presentation aspects and can be used in the learning process.Keywords: Chemical Module, POE (Predict, Observe, Explain), Colligative Properties ofSolutionJOM